Short Term Oral Methylergonovine Maleate Prophylaxis for Status Migrainosus. Case Series and Review of Literature - Haque, Najiya; Tariq, Nauman (Frontiers in Neurology, 2019)
Background: Intravenous dihydroergotamine (DHE) is frequently used during inpatient hospitalizations or outpatient infusion therapies for 3–5 days in order to break the continuous cycle of status migrainosus. We tried a short term 7 days prophylaxis of oral methylergonovine after discharge in order to prevent status migrainosus relapse and extend the therapeutic benefit from IV DHE. Methods: Patients were diagnosed with status migrainosus in clinic setting based on the ICHD-III criteria. They received 1 mg IV DHE every 8 h along with metoclopramide for 3–5 days followed by methylergonovine maleate oral tablets as prophylaxis for 7 days post discharge. They were asked to maintain their headache diaries which included data on headache frequency and intensity. A post discharge follow up at 1 and 68 weeks was planned. Clinical improvement was defined as >50% decrease in frequency and intensity of headaches. Intensity was graded on verbal numerical rating scale (VNRS) with 10 being the worst possible pain. The institutes IRB and ethics committee exempted this study from review given that it had only 3 patients. Results: A total of 3 patients 25–45 years of age who benefited from IV DHE, consented to trial of Methylergonovine Maleate 0.4 mg oral tablets three times a day prophylaxis on the day of discharge for a period of 7 days. At 1 week post discharge, all of the 3 patients had reported sustained improvement with severity dropping from an average of 8/10 intensity to 3/10 on VNRS. The headaches frequency had dropped from daily to episodic in 2 of the 3 patients. At an average of 7 weeks post discharge, 2 out of the 3 patients had reported sustained benefit. The third patient relapsed to the pre-admission status migrainosus severity. One patient reported mild diarrhea and nausea but was still able to continue the drug for a week. Conclusion: Methylergonovine maleate after 3–5 days of IV DHE infusions may be a feasible treatment strategy for status migrainosus. This approach has the potential to prolonged the benefit of IV DHE and prevent relapse in to status migrainosus.